Metodologi Ekonomi Islam - Yasmansyah Yasmansyah; Zulfani Sesmiarni (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
This study aims to analyze the thinking methods used in Islamic economics critically. This study assumes that the methods used in Islamic economics are mostly designed to determine Fallah. Islamic economics was born not as a separate discipline but as an integral part of the Islamic religion as complete life teaching. Islam guides all human activities, including economics. This research is library research with a qualitative approach. Sources of data in this study using secondary data derived from books and relevant research results. The results of this study found that the methodology of Islamic economics must be built on the principles of Islamic epistemology, produce scientific criteria, and convey Islamic values to others. Islamic economics has a complete scientific building, giving birth to theories that explain economic doctrine and reality.